Inhibition Test of Cassava Leaves (Manihot Esculenta Crantz) Flavonoid Nicotiflorin on Replication of Dengue Virus Serotype 1 in Vitro - Yulianti, Selsa; Apriyanto, Dadan Ramadhan; Brajawikalpa, Rama Samara; Dewi, Beti Ernawati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Dengue fever is a disease caused by the bite of Aedes aegypti mosquitoes infected with the dengue virus. Dengue virus infection can lead to hemorrhagic fever and even death. Currently, treatment for dengue infection is supportive, as there are no commercially available antiviral drugs. Nicotiflorin, a compound found in cassava leaves (Manihot esculenta Crantz), has shown potential as an antiviral agent against dengue. Aims: This study aimed to determine the inhibitory effect of the flavonoid nicotiflorin, derived from cassava (Manihot esculenta Crantz) leaves, as an antiviral agent against dengue virus serotype 1 (DENV-1) in vitro. Methods: A post-test-only control group design was utilized in this experimental research, comprising one control group alongside thirteen treatment groups. For the cytotoxicity assessment, the treatment groups were exposed to seven varying concentrations (1.25 µg/mL, 2.5 µg/mL, 5 µg/mL, 10 µg/mL, 20 µg/mL, 40 µg/mL, and 80 µg/mL), while six different concentration levels (1.5 µg/mL, 3.125 µg/mL, 6.25 µg/mL, 12.5 µg/mL, 25 µg/mL, and 50 µg/mL) were employed in the inhibition assay. The control group received 0.2% DMSO as a negative control. Antiviral inhibition was assessed using the Focus Forming Unit (FFU) Assay, while cytotoxicity was evaluated using the Microtiter Tetrazolium Assay (MTT Assay). Statistical analyses included the Shapiro-Wilk test for normality, the Kruskal-Wallis test for hypothesis testing, and post-hoc analysis to assess significant differences among treatment groups. Results: The CC₅₀ and IC₅₀ values of nicotiflorin from cassava leaves were determined to be 19.24 μg/mL and 0.9550 μg/mL, respectively, yielding a Selectivity Index (SI) of 20.14. These findings indicate that the flavonoid nicotiflorin from cassava leaves exhibits selective antiviral activity against DENV-1 replication. Statistical analysis revealed a non-normal data distribution (P < 0.05), a significant difference among groups based on the Kruskal-Wallis test (P < 0.05), and no statistically significant differences among specific concentrations in the post-hoc test. Conclusion: Nicotiflorin from cassava leaf (Manihot esculenta Crantz) has inhibitory activity on the replication of dengue virus serotype 1 strain in vitro.